Respuesta :
6x - 3 = -51
6x - 3+3 = -51 + 3
6x = -48
[tex] \frac{6x}{6} [/tex] = [tex] \frac{-48}{6} [/tex]
x = -8
6x - 3+3 = -51 + 3
6x = -48
[tex] \frac{6x}{6} [/tex] = [tex] \frac{-48}{6} [/tex]
x = -8
You have to move the -3 to the other side to leave the 6x alone. Since you are moving it, it will become a positive. Now it should be 6x= -51+3, or 6x= -48. You now want to leave the x alone so you divide by 6. (6x/6=-48/6) It should be equal to -8. Remember the signs are different so it has to be a negative answer!